Universality of Selected Components of the Japanese Economic Culture in the Area of Corporate Social Responsibility - Ściborska, Izabela (Ocena uniwersalności elementów japońskiej kultury ekonomicznej w zakresie społecznej odpowiedzialności przedsiębiorstw, 2010)
The article focuses on the contribution of Japanese economic culture into the Caux Round Table Principles of Business and attempts to quantify the principles developed and to test them against the realities of Polish small and medium business. It starts with a presentation of Japanese economic culture at both the state and company levels. Then it goes on to present the historical background and main premises of the Caux Round Table. The final part presents the outcome of an attempt to use the principles developed there to assess the awareness and attitudes of Polish entrepreneurs. The article aspires to answer the questions regarding the universality level of Caux Round Table Principles and their applicability to a region with its own, local business culture. The analysis covers the results of empirical studies, carried out by the author in the years 2006-2008 thanks to a scholarship received under the Integrated Regional Development Programme.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 134, s. 191-203
Keywords: economic culture; corporate social responsibility; Japan